2019
DOI: 10.1111/1440-1681.13192
|View full text |Cite
|
Sign up to set email alerts
|

Naegleria fowleri: Sources of infection, pathophysiology, diagnosis, and management; a review

Abstract: Naegleria fowleri, a thermophilic flagellate amoeba known as a “brain‐eating” amoeba, is the aetiological agent of a perilous and devastating waterborne disease known as primary amoebic meningoencephalitis (PAM), both in humans as well as in animals. PAM is a rare but fatal disease affecting young adults all around the world, particularly in the developed world but recently reported from developing countries, with 95%–99% mortality rate. Swimmers and divers are at high risk of PAM as the warm water is the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 93 publications
(246 reference statements)
2
103
0
5
Order By: Relevance
“…Epidemiologic studies of PAM indicate an estimate of 300-440 cases worldwide [3,6], with more than one third of the cases diagnosed in the United States [7]. However, this number may not exactly reflect the real number as some researchers propose an underestimation of the disease of up to 50% in this country, even when using well-established diagnostic methodologies and researchers with huge knowledge in different aspects related to PAM.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies of PAM indicate an estimate of 300-440 cases worldwide [3,6], with more than one third of the cases diagnosed in the United States [7]. However, this number may not exactly reflect the real number as some researchers propose an underestimation of the disease of up to 50% in this country, even when using well-established diagnostic methodologies and researchers with huge knowledge in different aspects related to PAM.…”
Section: Discussionmentioning
confidence: 99%
“…Naegleria fowleri infects humans by passing the nerves and entering the cribiform plate. After that, the amoebae have free entrance to the brain causing inflammation and necrosis 2 , 6 8 . Hence, the fulminant nature of this infection which normaly manifests in the patient with symptons such as intense headache, temperature, seizures and stiff neck.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the fulminant nature of this infection which normaly manifests in the patient with symptons such as intense headache, temperature, seizures and stiff neck. In the final stage of the disease, patients have been reported to suffer from hallucinations and paralysis previous reaching coma and death 6 8 . Furthermore, the average time of symptoms appearance after infection starts 1–9 days after exposure to contaminated water sources whereas patient death average is 1–18 after symptoms begin 4 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, PAM is considered a serious public health problem due to the previously mentioned high mortality rate [ 7 , 10 , 11 ]. Interestingly, a recent study showed that in Pakistan between 2008 and 2017, more than 100 cases were reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, around 11 cases of PAM have been reported from 1984 to 2007 [ 12 , 13 , 14 , 15 , 16 , 17 ]. Unfortunately, there are many cases underdiagnosed around the world due to lack of awareness of the disease or the similarity of clinical symptoms with other more common central nervous systemdiseases such as bacterial meningitis and viral encephalitis [ 6 , 18 ].…”
Section: Introductionmentioning
confidence: 99%